IPad for Digital Photographers. - Story, Derrick (Wiley, 2013)
Discover innovative ways to strengthen your photography business with your iPad Many photographers are turning to the flexible, easy-to-use tools of the iPad and relying on them to wear a variety of hats in their photography business. Whether portable portfolio, editing tool, payment-tracking system, or appointment calendar, the iPad melds together the best attributes of the cell phone and a laptop computer and this unique book highlights them all. With this helpful resource, you'll learn how to get the most out of your iPad to not only improve your business but also enhance your p.